2021
DOI: 10.1177/02841851211006918
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes on diagnostic performance of computed tomography angiography of the calf arteries in acute limb ischemia

Abstract: Background Patients with diabetes mellitus (DM) have a more extensive distal arterial occlusive disease compared to non-diabetic patients. Diagnostic imaging is a necessity to identify the location and extent of the arterial occlusion in acute limb ischemia (ALI). Computed tomography angiography (CTA) is the most commonly used modality and the diagnostic performance with CTA of calf arteries may be questioned. Purpose To evaluate diagnostic performance of CTA of calf arteries in ALI and to compare patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As it was mentioned before, one of the main disadvantages is an impression of more prominent stenosis due to severe vessel calcification. Patients with ALI are commonly seen with diabetes and diabetes is associated with heavy calcified peripheral vessels [20]. Calcium-induced artefacts limit the vision of the stenosis-free lumen of the vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mentioned before, one of the main disadvantages is an impression of more prominent stenosis due to severe vessel calcification. Patients with ALI are commonly seen with diabetes and diabetes is associated with heavy calcified peripheral vessels [20]. Calcium-induced artefacts limit the vision of the stenosis-free lumen of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-energy CTA can provide enhanced diagnostic features to differentiate between calcium deposits on the vessels and iodinated contrast. Studies showed that dual-energy CTA is more precise in imaging heavily calcified vessels [7] [20].…”
Section: Discussionmentioning
confidence: 99%